IMPROVING READING COMPREHENSION OF VIII GRADE STUDENTS AT SMP NEGERI 3 TOLITOLI THROUGH TASK BASED LEARNING - Inda Indrawati (Universitas Madako Tolitoli, 2019)
The students of SMP Negeri 3 Tolitoli had problem when they read the text. This research aims improving the reading comprehension of VIII grade students at SMP Negeri 3 Tolitoli through Task Based Learning. This is pre- experimental research design. The sample was 31 students at class VIIIH. The data were collected through observation, pretest, and posttest. The pretest was conducted to know the students’ prior knowledge before treatment, whereas posttest was accomplished to measure their knowledge after treatment. The researcher analyzed the data statistical. The result of the test showed that the students’ mean score in posttest 72.29 is higher than pretest 60.81. The testing hypothesis shows t-count 14.36 was higher than t-table 2.042. It indicates that null hypothesis (Ho) rejected and the alternative hypothesis (Ha) accepted. In other words, the students’ reading comprehension can be improved through Task Based Learning.Key Words: Improving, reading comprehension, and Task Based Learning.